(untitled) (Carte Romanze, 2016)
This article examines a recently discovered prose version of the Ordene de Chevalerie which is interpolated in only two of the 51 surviving manuscripts of the Old French translation of William of Tyre (the Eracles): Baltimore, Walters Art Gallery, ms. 137 and Épinal, Bibliothèque municipale, ms. 45. Discussion of the interpolation and of the broader manuscript context throws light both on the adaptable nature of the OC itself and on the preoccupations and tone of the French translation of William of Tyre in which it is included. An edition of the text of the OC as found in the Baltimore ms. follows the article. Questo saggio si occupa di una versione in prosa recentemente scoperta dell’Ordene de Chevalerie, inserita in solo due dei 51 manoscritti ancora esistenti della traduzione in francese antico della cronaca di Guglielmo di Tiro (Eracles): Baltimore, Walters Art Gallery, ms. 137 ed Épinal, Bibliothèque municipale, ms. 45. L’analisi dell’interpolazione e del suo piú ampio contesto manoscritto fa luce sia sulla la natura versatile dell’OC, sia sulle finalità e il tono della traduzione di Guglielmo di Tiro nella quale si trova inserita. Dopo lo studio, si presenta un’edizione del testo dell’OC secondo il manoscritto di Baltimora.